Enhancing active learning in large classes using web clicker - Woldemichael, D.E. (Universiti Putra Malaysia, 2018)
This paper presents the use of free web clicker (webclicker.org) to enhance active learning in large classroom. Web clicker platform works on any internet accessible device such as phones, pads, PCs, and laptops, without the need to purchase the clicker (hardware). The author used web clicker as pre/during/post lecture activity through concept questions. This helped to conduct formative assessment and identify misconceptions. The students also responded without peer pressure. To assess the effectiveness of using web clicker in enhancing active learning, surveys on two batches of students taking the same course in different time frame was conducted. An online survey with questionnaire consisting of five items on five-point Likert scale was used for which there were 47 respondents out of 127 students in the first batch and 76 respondents out of 151 students in the second batch. In addition, surveys through open-ended questions to get students' perception about the overall teaching and learning process were conducted. The overall result of the surveys was positive and in line with what was reported in literature. Web clicker encourages students to participate in the learning activity and motivates them to study. Â© Universiti Putra Malaysia Press.